Pengaruh PDRB, Investasi, Dan Jumlah Penduduk Terhadap Pendapatan Asli Daerah - Annas Nashiruddin; Banu Witono (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Local Revenue (PAD) is a vital financial source for regional governments, playing a crucial role in supporting development and public services at the local level. This research aims to investigate the influence of Regional Gross Domestic Product (RGDP), Investment, and population size on Local Revenue (PAD) in Regencies/Cities in Central Java for the fiscal years 2019-2021. The sample comprises all Regencies/Cities in Central Java Province, totaling 35 (29 Regencies and 6 Cities), meeting the specified criteria. Multiple linear regression analysis is employed as the analytical method. Empirical findings indicate that RGDP has a significant impact on local revenue, whereas investment and population size do not influence local revenue. Keywords: Gross Regional Domestic Product (GRDP), investment, population size, local revenue